2019
DOI: 10.1371/journal.pone.0225390
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy-based predictors of non-adherence, non-persistence and reinitiation of antihypertensive drugs among patients on oral diabetes drugs in the Netherlands

Abstract: BackgroundAdherence to antihypertensive drugs in patients with diabetes is important. To support adherence, attention should be paid to the dynamic process of implementation, persistence and reinitiation of these drugs. We assessed non-adherence, non-persistence and reinitiation patterns for antihypertensive drugs in patients on oral diabetes drugs and identified pharmacy-based predictors of these processes.MethodsWe conducted a cohort study in patients on oral diabetes drugs who initiated antihypertensive dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…Therefore, the physician’s explanation of the importance of lifelong administration of antiplatelet agents in PAD patients is of particular importance. In contrast to our results, Alfian et al [ 31 ] reported a longer duration of persistence to be a predictor of reinitiation. Their study was focused on the analysis of pharmacy-based predictors of nonadherence, nonpersistence, and reinitiation of antihypertensive drugs among patients on oral diabetes drugs.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, the physician’s explanation of the importance of lifelong administration of antiplatelet agents in PAD patients is of particular importance. In contrast to our results, Alfian et al [ 31 ] reported a longer duration of persistence to be a predictor of reinitiation. Their study was focused on the analysis of pharmacy-based predictors of nonadherence, nonpersistence, and reinitiation of antihypertensive drugs among patients on oral diabetes drugs.…”
Section: Discussioncontrasting
confidence: 99%
“…Earlier, Holvast et al showed that, with pharmacy dispensing data in the Netherlands, 10% of antidepressant users (ATC: N06A) discontinued therapy within a comparable period (the first four weeks) ( 24 ). Also based on pharmacy dispensing data, Alfian et al reported that 18% of diabetes patients in the North of the Netherlands stopped their cardiovascular drug treatment (ATC: C03, C07, C08 and C09) within the first year ( 25 ). Compared with both studies, our analysis was more specific, focusing on spironolactone and antidepressants that are registered with >10% risk for sADRs.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] In addition, we defined the basecase for the minimum period of medication use, which was referred to how long medications were taken, as 90 days and set the observation period of 3 years in the current study. 32…”
Section: Category (2): "Inclusion Criteria and Observation Period"mentioning
confidence: 99%